1984
DOI: 10.2307/2008290
|View full text |Cite
|
Sign up to set email alerts
|

Decay Rates for Inverses of Band Matrices

Abstract: Abstract. Spectral theory and classical approximation theory are used to give a new proof of the exponential decay of the entries of the inverse of band matrices. The rate of decay oí A'1 can be bounded in terms of the (essential) spectrum of A A* for general A and in terms of the (essential) spectrum of A for positive definite A. In the positive definite case the bound can be attained. These results are used to establish the exponential decay for a class of generalized eigenvalue problems and to establish exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(167 citation statements)
references
References 5 publications
2
164
0
1
Order By: Relevance
“…Under certain conditions this bottleneck can be removed. As was already mentioned above, the entries of the inverse of a nonsingular, banded matrix decay away from the main diagonal (see [6]). When the decay in the inverse of A is sufficiently rapid, the reduced matrix Z can be approximated by a block diagonal matrix Z with blocks of order 711 + in,,.…”
Section: ' ]mentioning
confidence: 73%
See 1 more Smart Citation
“…Under certain conditions this bottleneck can be removed. As was already mentioned above, the entries of the inverse of a nonsingular, banded matrix decay away from the main diagonal (see [6]). When the decay in the inverse of A is sufficiently rapid, the reduced matrix Z can be approximated by a block diagonal matrix Z with blocks of order 711 + in,,.…”
Section: ' ]mentioning
confidence: 73%
“…For simplicity, we assume that the half band width in = l = in,. We will use the notation [6], it can be shown that there are constants C and q, C > 0 and…”
Section: ' ]mentioning
confidence: 99%
“…Such a structure gives rise to a matrix E (be it G or A) that is sparse, symmetric, positive definite, and banded. For such matrices, it is well known in the literature that their inverse has entries whose values decay exponentially as one moves away from the diagonal [5]. We illustrate this property in Fig.…”
Section: Proposed Solutionmentioning
confidence: 85%
“…Yet, it is known that the inverse of a sparse matrix has many weak elements. This is shown analytically for band limited matrices in [14] and is expected to hold for all sparse matrices. This theoretical analysis means in practice that it should be possible to find sparse precoding matrices which approximate accurately the ZF precoder.…”
Section: Theory Of Sparse Approximate Inversesmentioning
confidence: 86%